Holographic thermodynamic relation for dissipative and non-dissipative universes in a flat FLRW cosmology - Nobuyoshi Komatsu (European Physical Journal C: Particles and Fields)
Abstract Horizon thermodynamics and cosmological equations in standard cosmology provide a holographic-like connection between thermodynamic quantities on a cosmological horizon and in the bulk. It is expected that this connection can be modified as a holographic-like thermodynamic relation for dissipative and non-dissipative universes whose Hubble volume V varies with time t. To clarify such a modified thermodynamic relation, the present study applies a general formulation for cosmological equations in a flat Friedmann–Lemaître–Robertson–Walker (FLRW) universe to the first law of thermodynamics, using the Bekenstein–Hawking entropy $$S_{\textrm{BH}}$$ S BH and a dynamical Kodama–Hayward temperature $$T_{\textrm{KH}}$$ T KH . For the general formulation, both an effective pressure $$p_{e}$$ p e of cosmological fluids for dissipative universes (e.g., bulk viscous cosmology) and an extra driving term $$f_{\Lambda }(t)$$ f Λ ( t ) for non-dissipative universes (e.g., time-varying $$\Lambda (t)$$ Λ ( t ) cosmology) are phenomenologically assumed. A modified thermodynamic relation is derived by applying the general formulation to the first law, which includes both $$p_{e}$$ p e and an additional time-derivative term $$\dot{f}_{\Lambda }(t)$$ f ˙ Λ ( t ) , related to a non-zero term of the general continuity equation. When $$f_{\Lambda }(t)$$ f Λ ( t ) is constant, the modified thermodynamic relation is equivalent to the formulation of the first law in standard cosmology. One side of this modified relation describes thermodynamic quantities in the bulk and can be divided into two time-derivative terms, namely $$\dot{\rho }$$ ρ ˙ and $$\dot{V}$$ V ˙ terms, where $$\rho $$ ρ is the mass density of cosmological fluids. Using the Gibbons–Hawking temperature $$T_{\textrm{GH}}$$ T GH , the other side of this relation, $$T_{\textrm{KH}} \dot{S}_{\textrm{BH}}$$ T KH S ˙ BH , can be formulated as the sum of $$T_{\textrm{GH}} \dot{S}_{\textrm{BH}}$$ T GH S ˙ BH and $$[(T_{\textrm{KH}}/T_{\textrm{GH}}) -1] T_{\textrm{GH}} \dot{S}_{\textrm{BH}}$$ [ ( T KH / T GH ) - 1 ] T GH S ˙ BH , which are equivalent to the $$\dot{\rho }$$ ρ ˙ and $$\dot{V}$$ V ˙ terms, respectively, with the magnitude of the $$\dot{V}$$ V ˙ term being proportional to the square of the $$\dot{\rho }$$ ρ ˙ term. In addition, the modified thermodynamic relation for constant $$f_{\Lambda }(t)$$ f Λ ( t ) is examined by applying the equipartition law of energy on the horizon. This modified thermodynamic relation reduces to a kind of extended holographic-like connection when a constant $$T_{\textrm{KH}}$$ T KH universe (whose Hubble volume varies with time) is considered. The evolution of thermodynamic quantities is also discussed, using a constant $$T_{\textrm{KH}}$$ T KH model, extending a previous analysis (Komatsu in Phys Rev D 108:083515, 2023).